The application of fuzzy sets theory to assess land suitability for wheat cultivation in the Meknes zone, Morocco - Amal Labaioui (African and Mediterranean Agricultural Journal - Al Awamia)
Land evaluation is a prerequisite for optimal land use and sustainable agricultural production. The FAO Land Evaluation Framework has defined an approach for assessing the suitability of land for cultivation in terms of coefficients ranging from very suitable (S1) to unsuitable (N). This assessment is based on soil properties and climatic data in relation to crop requirements. There are uncertainties in assigning a single suitability class to a unit of land because of spatial variability of properties and because a unit may belong to different suitability classes to different extents. To deal with this uncertainty when assigning suitability classes, fuzzy set theory has been proposed. In this study, we apply this theory and the geographic information system to assess land suitability for wheat cultivation in Meknes area and compare the results with those obtained using the FAO limiting combination method. The results show that the FAO method underestimates the suitability for 50% of the studied areas by assigning them the class S2 instead of S1 assigned by the fuzzy method. However, for both class S3 and N, the two methods are in perfect agreement. This study needs to be confirmed in next phase by a field work to assess which method is more adapted to Meknes region.